Mediators of repeat mammography in two tailored interventions for Iranian women - Fariba Farhadifar; Yamile Molina; Parvaneh Taymoori; Setareh Akhavan (BMC, 2016)
Abstract Background Many theory-based interventions exist that incorporate theoretical constructs (e.g., self-efficacy, behavioral control) believed to increase the likelihood of mammography. Nonetheless, little work to date has examined if increased screening among women receiving such interventions occurs due to changes in these targeted constructs. The aim of this study is to address this gap in the literature in the context of two interventions for improving regular screening among Iranian women. Methods A sample of 176 women over 50 years old in Tehran, Iran were randomly allocated into one of these three conditions: 1) an intervention based on Health Belief Model (HBM); 2) an intervention based on an integration of the HBM and selected constructs from the TPB (TPB); and 3) a control group (CON). Questionnaires were administered before the intervention and after a 6-month follow-up. The Preacher and Hayes method of mediation was used in analytic models. Results Changes in susceptibility, self-efficacy, and perceived control appeared to mediate HBM-CON differences in screening. Barriers attenuated the mediating effect of self-efficacy. Changes in barriers and self-efficacy appeared to mediate TPB-CON differences in screening. Conclusion This study was successful in identifying which theory-based constructs appear to underlie the effectiveness of HBM- and TPB-based interventions. Specific constructs have been identified that should be targeted in clinical practice to increase mammography practices among Iranian women.